TANGGUNG JAWAB KELOMPOK BERSENJATA NON-NEGARA DALAM KERANGKA HUKUM HUMANITER INTERNASIONAL - Yulindo Yulindo; Dinesh K. Dhankhar, Tarsisius Susilo, Muhammad Taufik Zega, Agustinus Adi Santoso (INTELIGENSIA MEDIA, 2025)
International Humanitarian Law (IHL) establishes the rules of war that must be followed by all parties to an armed conflict, whether states or non-state armed groups. Although non-state groups cannot ratify international treaties, the universal character of IHL and customary international law oblige them to respect humanitarian norms. This article examines the responsibilities of non-state armed groups under IHL, focusing on the Indonesian context (e.g., the Free Papua Movement) and comparing international cases such as Hamas (Palestine), the Taliban (Afghanistan), and FARC (Colombia). The research uses a normative legal methodology, analyzing international law instruments, academic literature, and reports by ICRC, HRW, and other organizations. The study finds that even if only states ratify treaties, Common Article 3 and customary rules bind all conflict parties, including non-state actors. The Hamas and Taliban cases illustrate IHL violations by non-state actors (for example, holding civilians hostage is a war crime), while Colombia’s peace deal with FARC shows the role of IHL in conflict resolution. In Indonesia, the armed conflict in Papua requires the TNI to apply IHL while upholding sovereignty, and TNI’s military operations against OPM are supported by national law and viewed as consistent with IHL. Although international enforcement against non-state actors is challenging (limited to national courts or mechanisms like the ICC), state parties have a duty to “respect and ensure respect” for IHL by all parties. Policy recommendations include strengthening domestic legislation on war crimes, enhancing IHL training for the TNI, and international cooperation for accountability.